The prevalence of abnormal Doppler's of the umbilical artery in a low-risk pregnant population in South Africa. (April 2021) - Hlongwane, TMAG; Cronje, T; Nkosi, BSS; Pattinson, RC
Abstract: Background: The assessment of fetal blood flow using Doppler waveform can be used to identify placental insufficiency, and hence is a tool to identify fetuses at risk of stillbirth due to fetal growth restriction (FGR). In South Africa the largest category of perinatal deaths is 'unexplained intrauterine death'. The majority of the mothers are clinically healthy women. This study was performed to determine the prevalence of abnormal umbilical resistance indices (abnormal RI) to see if screening a low-risk pregnant population is worthwhile. Methods: A descriptive study across 9 sites in 8 provinces of South Africa was performed to determine the prevalence of abnormal RI of the umbilical artery in women classified as having a low-risk pregnancy. The study was conducted from 1st September 2017- February 2020.The pregnant women classified were screened using a continuous wave Doppler ultrasound apparatus (Umbiflow™) between 28 and 34 weeks' gestation. Women with fetuses with an abnormal RI were referred to a high-risk clinic and were managed according to standard protocol. The outcomes of all the deliveries were recorded. Findings: Umbiflow™ screening of the umbilical artery was performed in 7088 women across nine sites; 919 (13·0%) fetuses had an abnormal RI. Absent end diastolic flow (AEDF) was found in 87 (1·2%) fetuses. The prevalence of small for gestational ages (SGA) babies was 23·1% in the normal RI group and was significantly higher in the abnormal RI group 32·1% ( p <0·0001). There was a statistical difference in the perinatal mortality rate between the normal RI (9.8/1000) and abnormal RI group (21.4/1000) [RR 0·046; 95% CI -0·06–0·98]. Interpretation: The prevalence of abnormal RI and AEDF in this screened low-risk population was about ten times higher than that previously recorded in high income countries. Continuous wave Doppler ultrasound screening detected previously undiagnosed growth restricted babies. The prevalence of AEDF warrants continuous wave Doppler ultrasound screening of the low-risk pregnant population in South Africa. Funding: This study was funded by the South African Medical Research Council (SAMRC) and the Council for Scientific and Industrial Research (CSIR)